Object Oriented Modeling of Optimal LSB-based Steganography for Secure Transmission of E-learning Documents - Banerjee, Soumendu (International Journal of Computer Sciences and Engineering, 2025)
In an e-learning system, all communications take places through Internet. When sender sends some secret documents to the receiver hiding them into the cover image, the image incorporates some sort of distortion, at the time of decompression. This LSB based steganographic approach will help the sender to send the documents after making compression and the receiver will receive the documents without having any sort of distortion. Here the proposed model has been wrapped in object oriented models to achieve the benefits of the object oriented approach